Long-term quality of life changes after primary septorhinoplasty - Bulut, Cem; Wallner, Frank; Kayser, Claire; Plath, Michaela; Plinkert, Peter K.; Baumann, Ingo (Quality of life research, 2018)
PurposeHealth-related quality of life measurements are gaining in importance in clinical medicine. Little is known about the long-term quality of life changes after septorhinoplasty. This study was designed to analyse the long-term quality of life impacts of septorhinoplasty, using disease-specific instruments—rhinoplasty outcome evaluation (ROE) and Functional Rhinoplasty Outcome Inventory-17 (FROI-17); as well as a generic instrument—Short-Form 36 Health Survey (SF-36).MethodsPatients completed the FROI-17, the ROE and the SF-36 preoperatively and at 12 and 60 months postoperatively. General demographic and clinical information (age, gender, allergies, medication, medical and surgical history) were collected from all patients.ResultsWe report a significant increase in disease-specific QOL after primary septorhinoplasty (as measured with the ROE & FROI-17) and in two scales of the SF-36 generic instrument (role-functioning physical and mental health) 1 year after surgery. Our patients showed further significant increase in disease-specific QOL (FROI-17) after their primary septorhinoplasty (1 year vs. 5 years postoperatively). SF-36 results showed significant improvements 5 years postoperatively (compared to preoperative scores) in six out of eight scales (physical functioning, role-functioning physical, bodily pain, vitality, social functioning and mental health).ConclusionSeptorhinoplasty can improve disease-specific and non-disease-specific QOL in the short- and long-term postoperative period. These improvements remain measurable 5 years after surgery.
Published online: 4 December 2017
Gesehen am 19.06.2018